Функції та дисфункції конфліктів на різних рівнях соціальної системи - Євтушенко, В. Р. (ХНУРЕ, 2020)
Modern society cannot exist without conflicts of interests, ideas and certain views. In a world where freedom of speech is of paramount importance, it is impossible to avoid differences of opinion that escalate into conflict situations. This study examines the role and importance of conflict in society, finding positive aspects of conflict of interest. This topic is very topical, as conflicts of interest arise constantly and many of them develop into clashes or have other negative consequences. In order to prevent such developments and to obtain a positive result, one must be able to control the development of conflicts
Keywords: філософія; дисфункції конфліктів